2017
DOI: 10.1108/jaoc-06-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diagnostic and interactive uses of management control systems and managerial coaching on reflection in teams

Abstract: Purpose -The goal of this study was to investigate the effects of managerial coaching, as well as interactive and diagnostic uses of management control systems (MCS), on reflection and critical reflection, which are important for team learning.Design/methodology/approach -Data were collected using a questionnaire survey.Hierarchical regression analyses were performed to test hypotheses using data from 235 employees in 50 teams from a Japanese automotive supplier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…10. Empirical results show a significant positive association between (critical team) reflection and an interactive use of MCS (Matsuo and Matsuo, 2017). …”
Section: Notesmentioning
confidence: 99%
“…10. Empirical results show a significant positive association between (critical team) reflection and an interactive use of MCS (Matsuo and Matsuo, 2017). …”
Section: Notesmentioning
confidence: 99%
“…While there are no studies explicitly investigating the relationship between the levers and the degree of emergence of PD strategies, a few studies have addressed the relationship of the levers with the strategy process at the organizational level. Arjaliès and Mundy (2013), Henri (2006), Kober et al (2007), Matsuo and Matsuo (2017) and Naranjo-Gil (2016) find that the interactive control systems are positively related to emergent strategies and to capabilities required for strategic change such as organizational learning, market orientation and critical reflection. This paper argues that the regular discussion of PD performance measures serves to challenge and critically assess PD processes, leading into new strategic initiatives.…”
Section: Theoretical and Empirical Background: Levers Strategy Formation And Innovativeness In The Product Development Functionmentioning
confidence: 99%
“…Accordingly, quality-related learning refers to the learning resulting from the quality management initiatives (Andersen and Lawrie, 2004), i.e. the outcomes of planned activities that use the context of quality to develop knowledge, skills and understandings, meaning that the organization has improved its awareness in relation to the quality management system (Freiesleben and Schwarz, 2006), serving as a building block of organizational learning (Matsuo and Matsuo, 2017). Freiesleben and Schwarz (2006) stated that, in essence, all improvement concepts claim that learning is a substantial part of quality initiatives, enabling companies to improve their quality in an increasingly efficient manner.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…as companies place more emphasis on diagnostic uses of the performance measurement system, they have an organization more amenable to learn. However, Matsuo and Matsuo (2017) showed that diagnostic use of management control systems is ineffective in stimulating regular reflection within teams, failing to promote single-loop learning.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation